Descriptive Study on Liver Cancer among Alcohol consumer and Smokers - Bhatta, Pramod; Khanal, Shankar P. (Nepal Journal of Multidisciplinary Research, 2021)
Liver cancer is one of the significant cancer types affecting the human population taking their lives. The study aimed to analyze the situation of liver cancer among alcohol consumers and smokers together, and it was conducted in BPKMCH, Chitwan. The data was collected from the year 2009 to 2013 AD. Randomly selected 160 cancer cases and analyzed the data. The finding suggested that most of the liver cancer patients drank alcohol and smoking cigarettes. The study indicated that there is still a need to investigate further the role of alcohol and smoking in the cancer genesis among them.